2008
DOI: 10.1124/mol.107.041988
|View full text |Cite
|
Sign up to set email alerts
|

Carmustine-Resistant Cancer Cells Are Sensitized to Temozolomide As A Result of Enhanced Mismatch Repair during the Development of Carmustine Resistance

Abstract: The cytotoxicity of the monofunctional alkylator temozolomide (TMZ) is mediated by mismatch repair (MMR) triggered by O 6 -alkylguanine, whereas MMR protects cells against bifunctional alkylators, including carmustine (BCNU). Therefore, TMZ may be cytotoxic to BCNU-resistant cancer cells because MMR affects sensitivity to TMZ and BCNU in a converse way. We evaluated TMZ cytotoxicity on BCNU-resistant variant (CEM-R) compared with the parental CCRF-CEM cell line (CEM-S). The mechanisms of its BCNU-resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Our previous study evaluated TMZ cytotoxicity in a BCNU-resistant variant leukemia cell line, in comparison with a BCNU-sensitive cell line (17). The study identified that the BCNU-resistant cells were more sensitive to TMZ compared with the BCNU-sensitive cells (17). In addition, the BCNU-resistant cells possessed increased hMLH1 and hMSH2 transcript levels (17).…”
Section: A B C D E Fmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study evaluated TMZ cytotoxicity in a BCNU-resistant variant leukemia cell line, in comparison with a BCNU-sensitive cell line (17). The study identified that the BCNU-resistant cells were more sensitive to TMZ compared with the BCNU-sensitive cells (17). In addition, the BCNU-resistant cells possessed increased hMLH1 and hMSH2 transcript levels (17).…”
Section: A B C D E Fmentioning
confidence: 99%
“…Intact MMR is required for the exertion of the cytotoxicity of TMZ, while interstrand crosslinks formed by bifunctional agents are, in part, repaired by MMR (21,27). Our previous study evaluated TMZ cytotoxicity in a BCNU-resistant variant leukemia cell line, in comparison with a BCNU-sensitive cell line (17). The study identified that the BCNU-resistant cells were more sensitive to TMZ compared with the BCNU-sensitive cells (17).…”
Section: A B C D E Fmentioning
confidence: 99%
See 3 more Smart Citations